Orbitofrontal Lesion Alters Brain Dynamics of Emotion-Attention and Emotion-Cognitive Control Interaction in Humans - Kuusinen, Venla; Cesnaite, Elena; Peräkylä, Jari; Ogawa, Keith H.; Hartikainen, Kaisa M. (Frontiers in Human Neuroscience, 2018)
Patients with lesion to the orbitofrontal cortex (OFC) experience challenges in emotional control and emotion-guided behaviors. The OFC is known to participate in executive function and attentional control of emotion and our previous research suggests OFC lesion alters the balance between voluntary and involuntary attention and cognitive control within the context of emotion. To better understand how OFC lesion affects the dynamics and interaction of these functions, we studied EEG and behavioral performance of 12 patients with lesion to the OFC and 11 control subjects with intact OFC in a Go/NoGo visual reaction time task with neutral targets and intervening threat-related emotional distractors (Executive RT test). Event-related potentials (ERP), specifically N2P3 peak-to-peak amplitude and the following late positive potential (LPP), were used to measure attention allocation and cognitive control to emotional distractors. Task performance and Behavioral Rating Inventory of Executive Functions - Adult version (BRIEF-A) scores were used to assess executive functions. As expected, the Control group showed increased N2P3 amplitude in the context of threat-related distractors, particularly over the right hemisphere, while LPP was not modulated by these distractors. In contrast, patients with OFC lesion showed no such impact of threat-related distractors on N2P3 amplitude but exhibited increased and prolonged left-lateralized impact of threat on LPP in the Go-condition. In NoGo-condition, the N2P3 amplitude was increased in both groups due to threat, but the impact was seen earlier, i.e. at the N2 peak in the OFC group and later at the P3 peak in Controls. The OFC group committed more errors in the Executive-RT test and reported more problems in BRIEF-A, thus both objective and subjective evidence for challenges in executive functions was obtained in patients with orbitofrontal lesion. Furthermore, the time-course of attention allocation and cognitive control towards task-irrelevant emotional stimuli was altered as evidenced by ERPs. We conclude that orbitofrontal lesion is associated with altered neural dynamics underlying the interaction of involuntary attention to emotion and cognitive control. These alterations in brain dynamics may underlie some of the challenges patients encounter in everyday life when emotional events interact with cognitive demands.